Assessment of Development Communication in a Globalised Context - Margaret Solo-Anaeto; Perpetua Ogechi Aondover; Timothy Ekeledirichukwu Onyejelem; Abdullahi Aliyu Maiwada (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2026)
This paper examines development communication within the context of globalisation, focusing on how global economic, technological, and cultural flows have reshaped communication strategies for social change. It interrogates the shifting paradigms of development communication from linear, top-down information dissemination models to more participatory, dialogic, and rights-based approaches that emphasise inclusion, local agency, and sustainability. Based on the qualitative review of scholarly literature, policy documents, and selected development interventions, the paper assesses the influence of globalisation on communication practices, particularly the role of digital media, transnational actors, and global development agendas. The paper argues that development communication is no doubt an important area of both academic and professional endeavour where several approaches can be harnessed to ensure development. While globalisation is a vital concept that has impacted both positively and negatively in various parts of the world, the role of communication in the globalisation process is enormous. This paper dissects the relationship between communication, globalisation, and development by analysing the roles played by each in the actualisation of the other. Globalisation was also dissected as a concept taking into cognizance its double-edged nature and divergent ideas of various scholars about the concept. The paper then related the concepts of communication, development and globalisation, especially in a practical context and further explained how development communication operates in a globalised context. It concludes that development outcomes are more sustainable when communication processes are people-centered and when global development narratives are adapted to local socio-cultural and political contexts.